Hubungan Antara Pencatatan Pelaporan Laporan Pemakaian-Lembar Permintaan Obat (LP-LPO) Dengan Perencanaan Obat Di Gudang Farmasi Dinas Kesehatan Kabupaten Manggarai - Theodorik Erik Nara; ELISMA ELISMA; PRISKA ERNESTINA TENDA (JURNAL INFO KESEHATAN, 2017)
The recording of drug data reporting at Regency/City Pharmacy is a series of activities in order to manage medicine in an orderly manner either medicine received, stored, distributed or used in health care unit such as Puskesmas. This study aims to calculate the highest number of drug use in Pharmaceutical Warehouse of Manggarai District Health Office based on LP-LPO reporting in 2012 and 2013, to know drug planning in 2013 and 2014 and to analyze the relationship between LP-LPO reporting in 2012 and 2013 with drug planning in 2013 and 2014. This type of research is descriptive research. The results showed that the most used drugs in 2012 and 2013 were Iron II sulfate tablet combination 13.92% and Ascorbic acid 500 mg tablet 21.69%. The drugs with the highest ranking in 2012 and 2013 are Antalgin 500 mg tablet 4.72% and Dexamethasone 0.5 mg tablet 3.40%. Drugs with the largest planning in 2012 and 2013 are Antacids DOEN combination tablets (655,000 tablets) and Amoxicillin 500 mg (1,148,000 tablets). The tenth-grade drug with the smallest planning of 2012 and 2013 is Iron II sulfate combination coated tablet (60,000 tablets in 2012 and 40,000 tablets in 2013. Record of LP-LPO reporting in 2012 with 2013 drug planning and LP-LPO reporting record in 2013 with Drug planning in 2014 has a fairly close relationship.